The Development of Cognitive Reappraisal From Early Childhood Through Adolescence: A Systematic Review and Methodological Recommendations - Willner, Cynthia J.; Hoffmann, Jessica D.; Bailey, Craig S.; Harrison, Alexandra P.; Garcia, Beatris; Ng, Zi Jia; Cipriano, Christina; Brackett, Marc A. (Frontiers in Psychology, 2022)
Cognitive reappraisal is an important emotion regulation strategy that shows considerable developmental change in its use and effectiveness. This paper presents a systematic review of the evidence base regarding the development of cognitive reappraisal from early childhood through adolescence and provides methodological recommendations for future research. We searched Scopus, PsycINFO, and ERIC for empirical papers measuring cognitive reappraisal in normative samples of children and youth between the ages of 3 and 18 years published in peer-reviewed journals through August 9th, 2018. We identified 118 studies that met our inclusion criteria. We first present a quantitative review of the methodologies used to investigate cognitive reappraisal in children and adolescents, with attention to variations in methodologies by the sample age range. We then present a qualitative review of findings with attention to: (1) the age at which children begin to effectively use cognitive reappraisal to regulate their emotions, and (2) developmental changes in cognitive reappraisal from early childhood through adolescence. We consider how methodological differences may contribute to inconsistencies in findings, highlight gaps in the literature that remain to be addressed, and make recommendations for future directions.